Voltage-sharing converter to supply single-phase asymmetrical four-level diode-clamped inverter with high power factor loads - Boora, A.; Nami, A.; zare, F.; Ghosh, Arindam; Blaabjerg, F. (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2010)
The output voltage quality of some of the single-phase multilevel inverters can be improved when their dc-link voltages are regulated asymmetrically. Symmetrical and asymmetrical multilevel diode-clamped inverters have the problem of dc-link capacitor voltage balancing, especially when power factor of the load is close to unity. In this paper, a new single-inductor multi-output dc/dc converter is proposed that can control the dc-link voltages of a single-phase diode-clamped inverter asymmetrically to achievevoltage quality enhancement. The circuit of the presented converter is explained and themain equations are developed. A control strategy is proposed and explained in details. To validate the versatilityof the proposed combination of the suggested dc–dc converter and the asymmetrical four-level diode-clamped inverter (ADCI), simulations and experiments have been directed. It is concluded that theproposed combination of introduced multioutput dc–dc converter and single-phase ADCI is a good candidate for power conversion in residential photovoltaic (PV) utilization.